An in‐vitro study on a novel six‐phage cocktail against multi‐drug resistant‐ESBL Shigella in aquatic environment. (28th November 2020) - Shahin, K.; Zhang, L.; Bao, H.; Hedayatkhah, A.; Soleimani‐Delfan, A.; Komijani, M.; He, T.; Barazandeh, M.; Mansoorianfar, M.; Bouzari, M.; Wang, R.
Abstract: Shigella spp. are water‐borne pathogens responsible for mild to severe cases bacilli dysentery all around the world known as Shigellosis. The progressively increasing of antibiotic resistance among Shigella calls for developing and establishing novel alternative therapeutic methods. The present study aimed to evaluate a novel phage cocktail of lytic phages against extended spectrum beta lactamase isolates of Shigella species in an aquatic environment. The phage cocktail containing six novel Shigella specific phages showed a broad host spectrum. The cocktail was very stable in aquatic environment. The cocktail resulted in about 99% decrease in the bacterial counts in the contaminated water by several species and strains of Shigella such as Shigella sonnei, Shigella flexneri and Shigella dysenteriae . Achieving such a high efficiency in this in‐vitro study demonstrates a high potential for in‐vivo and in‐situ application of this phage cocktail as a bio‐controlling agent against Shigella spp. contamination and infections. Abstract : Significance and impact of the study : Phages are being progressively used as an alternative treatment for antibiotic‐resistant bacteria. This report presents a new phage cocktail against MDR strains of Shigella species in aquatic environments. The cocktail was highly efficient in a sense that all of the tested Shigella isolates were infected by at least three of the phages at a high efficiency of plating. The cocktail remarkably decreased Shigella viable count by 99% in an aquatic environment.